2014
DOI: 10.1371/journal.pntd.0003005
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Sequencing and Developmental Regulation of Gene Expression in Anopheles aquasalis

Abstract: Background Anopheles aquasalis is a major malaria vector in coastal areas of South and Central America where it breeds preferentially in brackish water. This species is very susceptible to Plasmodium vivax and it has been already incriminated as responsible vector in malaria outbreaks. There has been no high-throughput investigation into the sequencing of An. aquasalis genes, transcripts and proteins despite its epidemiological relevance. Here we describe the sequencing, assembly and annotation of the An. aqua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 91 publications
0
7
0
Order By: Relevance
“…This observation suggests the presence of a catalytic mechanism of AMPs such as serine protease-endopeptidase in the intestine of A. darlingi (Marinotti et al 2013). Transcriptome analysis of A. aquasalis females fed with sugar showed the expression of trypsin-type peptidases (Costa-da-Silva et al 2014). Muller et al (1995 reported that A. gambiae expressed a set of seven trypsin genes, including antryp1 and antryp2, which are induced after feeding w i t h blood, while antryp3, antryp4, and antryp7 are constitutively expressed and undetectable after feeding with blood (Borges-Veloso et al 2015).…”
Section: Discussionmentioning
confidence: 89%
“…This observation suggests the presence of a catalytic mechanism of AMPs such as serine protease-endopeptidase in the intestine of A. darlingi (Marinotti et al 2013). Transcriptome analysis of A. aquasalis females fed with sugar showed the expression of trypsin-type peptidases (Costa-da-Silva et al 2014). Muller et al (1995 reported that A. gambiae expressed a set of seven trypsin genes, including antryp1 and antryp2, which are induced after feeding w i t h blood, while antryp3, antryp4, and antryp7 are constitutively expressed and undetectable after feeding with blood (Borges-Veloso et al 2015).…”
Section: Discussionmentioning
confidence: 89%
“…Differences in the expression of distinct serine peptidase-coding transcripts during the different developmental stages of An. aquasalis and between sugar- and blood-feeding females have been described [ 46 ]. In this work, we demonstrated the activity of trypsin-like serine peptidases in the midgut of sugar-feeding females and identified, by MS/MS, peptidases with molecular masses similar to those observed in the zymography, which suggested that these peptidases could be responsible for some of the observed proteolytic bands.…”
Section: Discussionmentioning
confidence: 99%
“…aquasalis females revealed the expression of trypsin-like peptidases. These enzymes have been suggested to be involved in the initial steps of blood digestion or could be related to the regulation of other trypsin genes [ 46 ]. Similarly, early works showed that An.…”
Section: Discussionmentioning
confidence: 99%
“…Protein tyrosine phosphatase, non-receptor type 9 (PTPN9) is a soluble tyrosine phosphatase that attenuates prolactin- and EGF-mediated STAT5 activation, which regulates expression of genes that promote cell survival and proliferation in breast cancer cells [ 12 ]. The levels of phosphorylated EGF also are enhanced upon inhibition of PTPN9-mediated by MicroRNA miR-24 [ 80 ]. Studies have shown that PTPN9, in addition to other prototypical tyrosine phosphatases, can down regulate insulin and leptin signal transduction [ 80 ].…”
Section: Ptpn9mentioning
confidence: 99%
“…The levels of phosphorylated EGF also are enhanced upon inhibition of PTPN9-mediated by MicroRNA miR-24 [ 80 ]. Studies have shown that PTPN9, in addition to other prototypical tyrosine phosphatases, can down regulate insulin and leptin signal transduction [ 80 ].…”
Section: Ptpn9mentioning
confidence: 99%